Evolution of agricultural law 50 years after the teoria della agrarietà - Malanos, Nancy L. (Przegląd Prawa Rolnego, 2022)
The existence or absence of general principles specific and exclusive to agricultural law that would justify its autonomy has been debated for years. Faced with the impossibility of identifying them, Antonio Carrozza proposed a change in the approach and searched for the foundations of autonomy within specific legal institutions that could be grouped under the common denominator of agrarietà, thus giving birth, in 1972, to his theory of agrarietà based on the biological cycle. Nowadays, the autonomy of agricultural law is undisputed. In fact, its constant evolution has been studied for years and the question we, like Professor Roman Budzinowski, ask is: what is agricultural law today?